Introduction to the OTL Special Issue: Highlighting AERA’s Online Teaching and Learning SIG 2023 - Lowenthal, Patrick; Moore, Robert (Online Learning, 2023)
Since 2016, the Online Learning Journal (OLJ), the official journal of the OLC, has released a special issue to extend opportunities for SIG OTL members to contribute their expertise in online education research. The 16 papers selected for this issue represent innovative and diverse topics using various research methods. We have tried to group them into five themes: 1. Measurement and analysis; 2. Equity, Inclusion, Advocacy, Embodiment; 3. Modality; 4. Openness; and 5. Philosophy & Theory.